Physiological demand among women touch football player in Kuala Lumpur / Muhammad Zulkifli Ismail - Ismail, Muhammad Zulkifli (2015)
The objective of this study is determining the highest performance level in the components of physiological demand among women's touch football player in Malaysia. Forty women touch football player in Malaysia (n=40) that were played in Mont's Kiara International School Touch Open were selected. Method: This study used purposive random sampling. Three teams were chosen for this tournament. The range of the subject's age was between 18 to 25 years old. All of the forty subject (n=40) from three teams (Tigress, Scorpion and UKM Bandit) has given six different tests in different components of physical fitness and skill testing, which are speed (30m speed test), agility (Illinois agility test), cardiovascular endurance (bleep test) and skills testing (L running and skip test, passing accuracy 4m, and hand speed). Result: The data were analyzed by using SPSS version 20. The descriptive statistic was used to asses the mean and standard deviation for all of the tests given. The result showed, speed (mean=5.70, sd= ±0.91), agility (mean= 20.26, sd= ±2.29), cardiovascular endurance (mean= 7.59, sd= ±0.90), L running and skip pass (mean=5.47, sd= ±0.71), passing accuracy 4m (mean= 9.62, sd= ±0.67), and hand pass (mean= 12.53, sd= ±1.96). Conclusion: This study has presented some anthropometric and physiological data for Malaysian women Touch players. This was the first research project in the sport of Touch in Malaysia. Such data can be used as a point of reference to assist coaches and women Touch players in Malaysia to better prepare for this sport. These findings can also be used by sports scientist as a guideline towards further research.